NILAI MALONDIALDEHID HEPAR MENCIT YANG DIINDUKSI PARASETAMOL PADA PEMBERIAN EKSTRAK METANOL KULIT KAYU Vitex pubescens Vahl - Anggraini, Wiwit; Rousdy, Diah Wulandari; Wardoyo, Elvi Rusmiyanto Pancaning (Universitas Tanjungpura, 2021)
Long-term consumption or overdose of paracetamol can induce liver damage characterized by increased measure of liver malondialdehyde (MDA). The methanol extract of laban tree bark (Vitex pubescens Vahl) contains antioxidant compounds such as flavonoids, tannins, and saponins that have potential as hepatoprotectors. This study aims to determine the optimal dose of methanol extract of V. pubescens tree bark to reduce liver MDA levels of mice after being induced by toxic dose of paracetamol (TDP). This study uses a completely randomized design (CRD) and 35 male Swiss strain mice aged 2,5-3 months. The treatments given consisted of normal control (aquades); negative control (TDP 105 mg/kg weight); positive control (vitamin E 48.6 mg/kg weight) and methanol extract of V. pubescens tree bark (75 mg/kg weight; 150 mg/Kg weight; 300 mg/kg weight and 600 mg/kg weight). Based on the research results, mice that were given an extract dose of 600 mg/kg weight showed a liver MDA levels of 0.68Â±0.24 nmol/mL which was close to the liver MDA levels of positive control mice, which was 0.62Â±0.12 nmol/mL.